What Do New University Students Actually Need To Know About Studying English? - Sandi Pradana (Journal on Education, 2022)
This study analyzes the need to learn English among new students at STIT Tanggamus. This analysis was carried out by distributing questionnaires to 100 respondents, consisting of new students. The study results showed that as many as 95% of respondents needed to learn English. In terms of importance, 89% of respondents stated that learning English is essential for their future. As many as 70% of respondents stated that they do not yet have good speaking skills and need help improving them. Based on these research findings, it can be concluded that the need to learn English is very high among new students at STIT Tanggamus. Therefore, educational institutions must provide adequate facilities and resources to meet these English learning needs.